Non-coding RNAs in cancer therapy-induced cardiotoxicity: Mechanisms, biomarkers, and treatments - Sun, Wanli; Xu, Juping; Wang, Li; Jiang, Yuchen; Cui, Jingrun; Su, Xin; Yang, Fan; Tian, Li; Si, Zeyu; Xing, Yanwei (Frontiers in Cardiovascular Medicine, 2022)
As a result of ongoing breakthroughs in cancer therapy, cancer patients' survival rates have grown considerably. However, cardiotoxicity has emerged as the most dangerous toxic side effect of cancer treatment, negatively impacting cancer patients' prognosis. In recent years, the link between non-coding RNAs (ncRNAs) and cancer therapy-induced cardiotoxicity has received much attention and investigation. NcRNAs are non-protein-coding RNAs that impact gene expression post-transcriptionally. They include microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs). In several cancer treatments, such as chemotherapy, radiotherapy, and targeted therapy-induced cardiotoxicity, ncRNAs play a significant role in the onset and progression of cardiotoxicity. This review focuses on the mechanisms of ncRNAs in cancer therapy-induced cardiotoxicity, including apoptosis, mitochondrial damage, oxidative stress, DNA damage, inflammation, autophagy, aging, calcium homeostasis, vascular homeostasis, and fibrosis. In addition, this review explores potential ncRNAs-based biomarkers and therapeutic strategies, which may help to convert ncRNAs research into clinical practice in the future for early detection and improvement of cancer therapy-induced cardiotoxicity.